Addressing the Transnistrian conflict: competing stances of Moldova's political parties and expert community - Protsyk, Oleh; Volentir, Andrei; Bucãtaru, Igor (2007)
Abstract: 'The Transnistrian conflict continues to be one of the most important issues facing political parties and the expert community in Moldova. Since the start of the post-communist transition period, political parties have routinely felt the necessity to articulate their approaches to solving the conflict. During both electoral and inter-electoral periods, the Transnistrian issue has occupied a special position on the country's political agenda. This has required political parties to take a stance on the issue. Similarly, the country's expert community, which includes academics, political analysts, and media commentators, has struggled with the need to explain and interpret the conflict to their audiences. In presenting such interpretations for the general public, they could not avoid formulating their own positions on potential causes of and solutions to the conflict. The authors here employ elite survey techniques as one approach to analyzing the variation in political parties' and e